Where youth and laughter go - Folsom, Seth W. B., 1972- (Annapolis, Maryland)
xxii, 368, [2] sayfa
Keywords: “Where Youth and Laughter Go completes LtCol Seth Folsom's recounting of his personal experiences in command over a decade of war. It is the culminating chapter of a trilogy that began with The Highway War: A Marine Company Commander in Iraq in 2006 and continued with In the Gray Area: A Marine Advisor Team at War in 2010. The chronicle of Folsom's command of 3rd Battalion, 7th Marine Regiment, “The Cutting Edge,“ and his harrowing deployment to Afghanistan's volatile Sangin District presents a deeper look into the complexities and perils of modern counterinsurgency operations in America's longest war. Charged with the daunting task of pacifying a region with a long history of violence and instability, Folsom and his Marines struggled daily to wage a dynamic campaign against the shadowy enemy force that held Sangin's population firmly in its grip. With peace and stability always teetering on the brink of collapse, the Marines of “The Cutting Edge“ confronted their own mortality as they conducted endless patrols through Sangin's minefields while fighting to win the hearts and minds of the Afghan villagers. No other books have been published from the perspective of a Marine infantry battalion commander in Afghanistan. It was Folsom's job, as the unit commander, to lead his Marines under impossible circumstances. LtCol Folsom made the unusual decision to patrol with his rifle squads every day through Sangin, where his Marines dodged improvised explosive devices and sniper fire from an invisible enemy. As his tour progressed and casualties mounted, he found his objectivity evaporating and the love for his men growing. Where Youth and Laughter Go is more than a blood-and-guts war story, it is a jarring, “boots on the ground“-level examination of the myriad challenges and personal dilemmas that today's young service members face as the United States approaches its final endgame in Afghanistan“--